The contributions of cancer cell metabolism to metastasis - Gloria Pascual; Diana Domínguez; Salvador Aznar Benitah; Almut Schulze; Mariia Yuneva (The Company of Biologists, 2018)
Metastasis remains the leading cause of cancer-related deaths worldwide, and our inability to identify the tumour cells that colonize distant sites hampers the development of effective anti-metastatic therapies. However, with recent research advances we are beginning to distinguish metastasis-initiating cells from their non-metastatic counterparts. Importantly, advances in genome sequencing indicate that the acquisition of metastatic competency does not involve the progressive accumulation of driver mutations; moreover, in the early stages of tumorigenesis, cancer cells harbour combinations of driver mutations that endow them with metastatic competency. Novel findings highlight that cells can disseminate to distant sites early during primary tumour growth, remaining dormant and untreatable for long periods before metastasizing. Thus, metastatic cells must require local and systemic influences to generate metastases. This hypothesis suggests that factors derived from our lifestyle, such as our diet, exert a strong influence on tumour progression, and that such factors could be modulated if understood. Here, we summarize the recent findings on how specific metabolic cues modulate the behaviour of metastatic cells and how they influence the genome and epigenome of metastatic cells. We also discuss how crosstalk between metabolism and the epigenome can be harnessed to develop new anti-metastatic therapies.